1999
DOI: 10.1007/s004310051203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new treatments for respiratory failure on outcome of infants with congenital diaphragmatic hernia

Abstract: Management based on early HFOV, eventually associated with surfactant, iNO and ECMO to achieve preoperative stabilisation, resulted in a good survival rate (89%) and good neurodevelopmental outcome at 1 year of age in infants with CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 26 publications
1
43
0
1
Order By: Relevance
“…16 Quality of included studies Our search identified retrospective, single-center case series or case vs historical control comparisons, raising the possibility of both selection and performance bias. [16][17][18][19][20][21][22][23][24][25][26][27] The improvement in outcomes noted in reports comparing serial epochs are accompanied by reports of changes in clinical practice. Details of various practices (specifics of antenatal care, ventilation strategy, PPHN management strategy and use of ECMO) were not uniformly recorded in all studies.…”
Section: Selection Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…16 Quality of included studies Our search identified retrospective, single-center case series or case vs historical control comparisons, raising the possibility of both selection and performance bias. [16][17][18][19][20][21][22][23][24][25][26][27] The improvement in outcomes noted in reports comparing serial epochs are accompanied by reports of changes in clinical practice. Details of various practices (specifics of antenatal care, ventilation strategy, PPHN management strategy and use of ECMO) were not uniformly recorded in all studies.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Survival for isolated CDH for the successful centers was 560/661 (85%; range: 78 to 96%). [15][16][17][18][19][20][22][23][24][25]27 Reported survival for isolated CDH using conventional medical management, excluding ECMO but including high-frequency ventilation was 331/367 (90%; range: 83 to 100%). The frequency of ECMO use for isolated CDH was 251/622 (40%; range: 11 to 61%), and overall survival for infants with isolated CDH placed on ECMO was 149/206 (73%; range: 33 to 86%; Table 1).…”
Section: Survivalmentioning
confidence: 99%
See 3 more Smart Citations